Controlled weakening of model ice: Replicating the mechanical response of summer-warmed sea ice in laboratories and test basins - N. Fuchs; F. von Bock und Polach; P. Buil; S.M. Isay; D. Notz; L. Nupnau; N. Reimer; L. Schoepflin; T. Zorn (Ocean Engineering, 2026)

Watershed Continuum Monitoring Approach: combining multiple water quality patterns along stream and river flowpaths to track sources, pathways, and processing of pollutants - Sujay S. Kaushal; Ashley E. Mon; Stanley B. Grant; Paul M. Mayer; Aaron J. Porter; Andrew J. Sekellick; Jason H. Chase; Shantanu V. Bhide; John D. Jastram; Tamara A. Newcomer-Johnson; Sydney A. Shelton; Alexis M. Yaculak; et al. (Ecological Engineering, 2026)

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

High abundances of zooxanthellate zoantharians (Palythoa and Zoanthus) at multiple natural analogues: potential model anthozoans? - James Davis Reimer; Sylvain Agostini; Yimnang Golbuu; Ben P. Harvey; Michael Izumiyama; Emmeline A. Jamodiong; Erina Kawai; Hajime Kayanne; Haruko Kurihara; Timothy Ravasi; Shigeki Wada; Riccardo Rodolfo-Metalpa (Coral Reefs, 2023)

DNA metabarcoding confirms primary targets and breadth of diet for coral reef butterflyfishes - Darren J. Coker; Joseph D. DiBattista; Michael Stat; Roberto Arrigoni; James Reimer; Tullia I. Terraneo; Rodrigo Villalobos; Jessica P. Nowicki; Michael Bunce; Michael L. Berumen (Coral Reefs, 2023)

Insights Into Sea Turtle Population Composition Obtained With Stereo-Video Cameras in situ Across Nearshore Habitats in the Northeastern Gulf of Mexico - Tabitha Siegfried; Christopher Noren; Jackson Reimer; Matthew Ware; Mariana M. P. B. Fuentes; Susan E. Piacenza (Frontiers in Marine Science, 2021)
Population size estimates are key parameters used in assessments to evaluate and determine a species’ conservation status. Typically, sea turtle population estimates are made from nesting beach surveys which capture only hatchling and adult female life stages and can display trends opposite of the full population. As such, in-water studies are critical to improve our understanding of sea turtle population dynamics as they can target a broader range of life stages – though they are more logistically and financially challenging to execute compared to beach-based surveys. Stereo-video camera systems (SVCS) hold promise for improving in-water assessments by removing the need to physically capture individuals and instead extract 3D measurements from video footage, thereby simplifying monitoring logistics and improving safety for the animals and surveyors. To demonstrate this potential, snorkel surveys were conducted at artificial habitats in the northeastern Gulf of Mexico (neGOM) to collect size and photo-identification data on sea turtles in situ using a SVCS. Over 29.86 survey hours, 35 sea turtles were observed across three species ( Caretta caretta, Chelonia mydas , and Lepidochelys kempii ) and all neritic life stages (juvenile, sub-adult, and adult) utilizing different habitats, including artificial reefs, jetties, and fishing piers. Greens straight carapace length ranged from 28.55 to 66.96 cm ( n = 23, mean 43.07 cm ± 11.26 cm standard deviation; SD) and loggerheads ranged from 59.71 to 91.77 cm ( n = 10, mean 74.50 cm ± 11.35 cm SD), and Kemp’s ridleys ranged from 42.23 cm to 44.98 cm (mean 43.61 cm ± 1.94 cm SD). Using a linear mixed model, we found that species and habitat type were the most important predictors of sea turtle body length distribution. Overall, this case study demonstrates the potential of SVCS surveys to enhance our understanding of the population structure of sea turtle species within the neGOM and elsewhere.

Low Static Shear Modulus Along Foliation and Its Influence on the Elastic and Strength Anisotropy of Poorman Schist Rocks, Homestake Mine, South Dakota - Katherine J. Condon; Hiroki Sone; Herbert F. Wang; J. Ajo-Franklin; T. Baumgartner; K. Beckers; D. Blankenship; A. Bonneville; L. Boyd; S. Brown; J. A. Burghardt; C. Chai; et al. (Rock Mechanics and Rock Engineering, 2020)

The Impact of Federal and State Conservation Programs on Farmer Nitrogen Management - Adam P. Reimer; Riva C. H. Denny; Diana Stuart (Environmental Management, 2018)

Sedimentology, structure and age estimate of five continental slope submarine landslides, eastern Australia - S. Clarke; T. Hubble; J. Webster; D. Airey; E. De Carli; C. Ferraz; P. Reimer; R. Boyd; J. Keene (Australian Journal of Earth Sciences, 2016)

Transplacental Transfer of Polychlorinated Biphenyls, Polybrominated Diphenylethers, and Organochlorine Pesticides in Ringed Seals (Pusa hispida) - T. M. Brown; P. S. Ross; K. J. Reimer (Archives of Environmental Contamination and Toxicology, 2016)

Transcending borders—integrating cell biology in the new Protoplasma - P. Nick; Reimer Stick (Protoplasma, 2014)

The diet of M yotis lucifugus across C anada: assessing foraging quality and diet variability - Elizabeth L. Clare; William O. C. Symondson; Hugh Broders; François Fabianek; Erin E. Fraser; Alistair MacKenzie; Andrew Boughen; Rachel Hamilton; Craig K. R. Willis; Felix Martinez‐Nuñez; Allyson K. Menzies; Kaleigh J. O. Norquay; et al. (Molecular Ecology, 2014)
Variation in prey resources influences the diet and behaviour of predators. When prey become limiting, predators may travel farther to find preferred food or adjust to existing local resources. When predators are habitat limited, local resource abundance impacts foraging success. We analysed the diet of Myotis lucifugus (little brown bats) from Nova Scotia (eastern Canada) to the Northwest Territories (north‐western Canada). This distribution includes extremes of season length and temperature and encompasses colonies on rural monoculture farms, and in urban and unmodified areas. We recognized nearly 600 distinct species of prey, of which ≈30% could be identified using reference sequence libraries. We found a higher than expected use of lepidopterans, which comprised a range of dietary richness from ≈35% early in the summer to ≈55% by late summer. Diptera were the second largest prey group consumed, representing ≈45% of dietary diversity early in the summer. We observed extreme local dietary variability and variation among seasons and years. Based on the species of insects that were consumed, we observed that two locations support prey species with extremely low pollution and acidification tolerances, suggesting that these are areas without environmental contamination. We conclude that there is significant local population variability in little brown bat diet that is likely driven by seasonal and geographical changes in insect diversity, and that this prey may be a good indicator of environment quality.

Farmer Participation in U.S. Farm Bill Conservation Programs - Adam P. Reimer; Linda S. Prokopy (Environmental Management, 2014)

Relative and Combined Effects of Selenium, Protein Deficiency and Ethanol on Hepatocyte Ballooning and Liver Steatosis - E. González-Reimers; M. J. Monedero-Prieto; J. M. González-Pérez; M. C. Durán-Castellón; L. Galindo-Martín; P. Abreu-González; M. J. Sánchez-Pérez; F. Santolaria-Fernández (Biological Trace Element Research, 2013)

Intratracheal Versus Intravenous Liposomal Delivery of siRNA, Antisense Oligonucleotides and Anticancer Drug - Olga B. Garbuzenko; Maha Saad; Seema Betigeri; Min Zhang; Alexandre A. Vetcher; Viatcheslav A. Soldatenkov; David C. Reimer; Vitaly P. Pozharov; Tamara Minko (Pharmaceutical Research, 2009)

Zoanthid diversity (Anthozoa: Hexacorallia) in the Galapagos Islands: a molecular examination - J. D. Reimer; F. Sinniger; C. P. Hickman (Coral Reefs, 2008)

Physiological and proteomic responses in Mytilus edulis exposed to PCBs and PAHs extracted from Baltic Sea sediments - Björne Olsson; Brian P. Bradley; Michael Gilek; Olof Reimer; Jenn L. Shepard; Michael Tedengren (Hydrobiologia, 2004)

SPM concentrations in the German Bight: comparison between a model simulation and measurements - W. Puls; J. Beusekom; U. Brockmann; R. Doerffer; U. Hentschke; P. König; D. Murphy; B. Mayer; A. Müller; Th. Pohlmann; A. Reimer; R. Schmidt-Nia; et al. (Ocean Dynamics, 1999)

Chemical Ozone Loss in the Arctic Winter 1994/95 as Determined by the Match Technique - M. Rex; P. Von Der Gathen; G.O. Braathen; N.R.P. Harris; E. Reimer; A. Beck; R. Alfier; R. Krüger-carstensen; M. Chipperfield; H. De Backer; D. Balis; F. O'Connor; et al. (Journal of Atmospheric Chemistry, 1999)

A Study of Ozone Laminae Using Diabatic Trajectories, Contour Advection and Photochemical Trajectory Model Simulations. - S. J. Reid; M. Rex; P. Von Der Gathen; I. Fløisand; F. Stordal; G. D. Carver; A. Beck; E. Reimer; R. Krüger-Carstensen; L. L. De Haan; G. Braathen; V. Dorokhov; et al. (Journal of Atmospheric Chemistry, 1998)